2013
DOI: 10.7785/tcrt.2012.500317
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Electroporation for Unresectable Hepatocellular Carcinoma: Initial Experience and Review of Safety and Outcomes

Abstract: The aims of this study were to evaluate the safety, feasibility and tumour response of irreversible electroporation, a non-thermal ablation technique, for the treatment of unresectable hepatocellular carcinoma. The endpoints were safety and local treatment efficacy.Patients with unresectable tumours and tumours not amenable for radiofrequency ablation because of their vicinity to organs vulnerable to thermal damage such as the bowel or because they were close to large blood vessels that would limit efficacy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(65 citation statements)
references
References 28 publications
4
59
0
2
Order By: Relevance
“…Except for transient postprocedural pain (64 %), no complications were observed in this study. At 6 mo, response evaluation revealed CR in a total of 72 % and 93 % of tumors ≤ 3 cm and the local progression-free survival (PFS) was 18 ± 4 mo and the distance PFS was 14 ± 6 mo [24]. The previous findings are also in line with the preliminary results of a prospective multicenter phase II trial conducted by Lencioni et al using IRE for the treatment of early stage HCC.…”
Section: Liversupporting
confidence: 80%
“…Except for transient postprocedural pain (64 %), no complications were observed in this study. At 6 mo, response evaluation revealed CR in a total of 72 % and 93 % of tumors ≤ 3 cm and the local progression-free survival (PFS) was 18 ± 4 mo and the distance PFS was 14 ± 6 mo [24]. The previous findings are also in line with the preliminary results of a prospective multicenter phase II trial conducted by Lencioni et al using IRE for the treatment of early stage HCC.…”
Section: Liversupporting
confidence: 80%
“…srč-na mišica. [17][18][19][20][21][22][23][24][25][26][27][28] V elektrokemoterapiji služi elektroporacija kot fizikalni dostavni sistem različnih učinkovin. Na ta način elektrokemoterapija omogoča povečan vnos molekul izbranega kemoterapevtika v tumorske celice.…”
Section: Elektroporacija V Elektrokemoterapijiunclassified
“…The Nanoknife ® (Angiodynamic, Latham, NY, USA) is commercially available for this purpose. Although the clinical data of IRE in the treatment of HCC are very limited, a recent study reported an 18-month recurrence-free survival for patients with unresectable HCCs treated by IRE [68].…”
Section: Other Ablation Modalitiesmentioning
confidence: 99%